Ricebean in Home Gardens of the Chitwan Valley - Khadka, Kamal; Khanal, Aditya R (Journal of Agriculture and Environment, 2013)
Ricebean is a neglected and underutilized grain legume grown in specific pockets by poor and marginal farmers. Despite being a multipurpose legume, its use in food, fodder and green manure crop were limited to farmers knowledge. Recognizing multiple use of ricebean a reconnaissance survey was conducted in Chitwan valley to assess the potential of ricebean as one of the home garden species in December 2007. Household survey was done to appraise the knowledge on ricebaean and its use. Agro-morphological traits were analysed. The study showed ricebean to be a new crop in the valley. Rice bean is helping the farmers to diversify their diet. Ricebean is also a good source of fodder and farmers believe that ricebean enriches soil fertility in the home gardens. Descriptive analysis of the agro-morphological traits showed diversity in the ricebean accessions grown by the farmers. The study clearly indicated that ricebean can be a potential crop in the home gardens of the Chitwan valley.